ANTIMICROBIAL ACTIVITY OF METHANOLIC EXTRACT OF MANGROVE BARK - POWAR P. S.; D. K. GAIKWAD (International Journal of Pharma and Bio Sciences, 2013)
Antimicrobial effect of the extract of three Indian mangrove plants of Avicennia officinalis (stem) Fam. Avicennaceae, Rhizophora mucronata, pior (root and stem) Fam. Rhizophoraceae and Sonneratia alba J Smith (stem) Fam. Sonneratiaceae bark were investigated. The crude extracts from dried barks of mangroves were extracted in methanol and obtained extracts were evaporatorted to concentrate. The extract obtained was evaluated for antimicrobial activity against bacteria by using agar well diffusion method and the zone of inhibition in diameters was measured. The standard extracts at the concentration of 50µg/ml exhibited antibacterial activity against test microorganism. The root of R. mucronata and stem extract of R. mucronata, S. alba and A. officinalis exhibits highest antimicrobial activity showing zone of inhibition in the range 21-39mm against all tested bacteria.